KAMPANYE DAN MENTORING KELAS POLIGAMI DALAM KASUS TREN DI INDONESIA : (Analisis Gerakan Sosial Accomodating Protest) - Anisa Isdiyanti Isdiyanti (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2024)
The pros and cons regarding the practice of polygamy are a discussion that will never cease to be debated by people in various parts of the world. Apart from the controversy regarding the issue of polygamy, the author found an online media site which is actively propagating the practice of polygamy, they call it the Polygamy Community, this community is expanding not only through offline activities in various regions, but also often exists to voice its understanding using online media. In this research the author will examine the motives of the Polygamous Community in Indonesia in terms of framing, opportunity structure and mobilization of the polygamous movement using the lens of social movement theory. The type of research is qualitative and empirical using descriptive analysis methods. The purpose of this article is to provide a literary understanding related to the polygamy campaign movement which is becoming a trend in Indonesia.